2016
DOI: 10.1021/acschembio.6b00269
|View full text |Cite
|
Sign up to set email alerts
|

Dark Hydrazone Fluorescence Labeling Agents Enable Imaging of Cellular Aldehydic Load

Abstract: Aldehydes are key intermediates in many cellular processes, from endogenous metabolic pathways like glycolysis to undesired exogenously induced processes such as lipid peroxidation and DNA interstrand cross-linking. Alkyl aldehydes are well documented to be cytotoxic, affecting the functions of DNA and protein, and their levels are tightly regulated by the oxidative enzyme ALDH2. Mutations in this enzyme are associated with cardiac damage, diseases such as Fanconi anemia (FA), and cancer. Many attempts have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 48 publications
(79 reference statements)
0
51
0
1
Order By: Relevance
“…44–46 Furthermore, numerous aldehydes and ketones (e.g., ketone bodies) 47 are generated through normal and pathogenic metabolism. 48 Specific conditions, like oxidative stress, 4951 are also known to trigger the production of a variety of aldehydes. Consequently, the concentration of cellular carbonyl compounds can span several orders of magnitude, from low nanomolar to high micromolar.…”
Section: Utility Of Oxime/hydrazone Ligationmentioning
confidence: 99%
See 2 more Smart Citations
“…44–46 Furthermore, numerous aldehydes and ketones (e.g., ketone bodies) 47 are generated through normal and pathogenic metabolism. 48 Specific conditions, like oxidative stress, 4951 are also known to trigger the production of a variety of aldehydes. Consequently, the concentration of cellular carbonyl compounds can span several orders of magnitude, from low nanomolar to high micromolar.…”
Section: Utility Of Oxime/hydrazone Ligationmentioning
confidence: 99%
“…As expected, the hydrolysis and transimination of hydrazones and oximes are significantly faster under acidic conditions and at elevated temperature. 48,128131 Senter and co-workers studied the release of the antimitotic agent auristatin E from a monoclonal antibody conjugate and found that the half-life time t 1/2 of the respective hydrazone linkage dropped from t 1/2 = 183 h at pH 7.2 to t 1/2 = 4.4 h at pH 5. 132 This can be a very useful feature for targeted drug delivery.…”
Section: Stability Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic efforts to decrease exposure to toxic reactive aldehydes are likely to be advanced by developing methods for measurement of these substrates Recently, a general sensor of reactive aldehydes and specific sensors of formaldehyde have been developed [9496]. The challenges for use of these sensors include the volatility of the aldehydic substrates, and the need for reactions to occur at physiological pH and temperature if they are to be applied to viable cells.…”
Section: Aldehyde Sensors To Monitor Substrate Levelsmentioning
confidence: 99%
“…The challenges for use of these sensors include the volatility of the aldehydic substrates, and the need for reactions to occur at physiological pH and temperature if they are to be applied to viable cells. We are presently validating the dark hydrazone sensor [96] for measurement of overall reactive aldehydes in HSC, with the goal of using this technology to detect differences in intracellular aldehyde levels in HSC or other cells from ALDH2*1 and ALDH2*2 individuals and to monitor the effects of ALDH2 activators on these levels, in anticipation of clinical trials.…”
Section: Aldehyde Sensors To Monitor Substrate Levelsmentioning
confidence: 99%